Analysis of the Implementation of the Principle of Honesty (Shiddiq) in Islamic Business Ethics in Herbal Business (Case Study of Harokah Herbal Shop Medan) - Muhammad Fathi Farhat; Muhammad Syukri Albani Nasution; Muhammad Ikhsan Harahap (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to analyze the implementation of the principle of honesty (shiddiq) in Islamic business ethics at Toko Harokah Herbal Medan and its implications for consumer trust and business sustainability. The study used a qualitative approach with a case study design. Informants consisted of 1 business owner, 3 senior agents (who had partnered for more than 2 years), and 5 loyal consumers (who had experienced the complaint-return process), selected through purposive sampling techniques. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results show that the principle of shiddiq has been consistently implemented through product information transparency, price transparency and agency systems, responsible product quality management, and honest handling of consumer complaints. A distinguishing aspect found is that Toko Harokah Herbal demonstrates the 'cost of honesty': when the business honestly disclosed during a supply shortage that stock was limited, rather than losing customers, this action actually strengthened agent loyalty through increased trust. The implementation of honesty contributes to reducing information asymmetry, increasing consumer and business partner trust, and strengthening customer loyalty. This study concludes that the principle of shiddiq is not only a moral value in Islamic business ethics but also an effective business strategy in creating competitive advantage and sustainable business growth in sharia-based MSMEs.